Vigabatrin associated retinal dysfunction in children with epilepsy. Issue 6 (1st December 2001) - Koul, R; Chacko, A; Ganesh, A; Bulusu, S; Al Riyami, K
Abstract : BACKGROUND: Recent reports have established that eye changes occur in patients treated with vigabatrin. AIM: To identify the eye changes associated with vigabatrin, based on a prospective study of children treated for seizures. METHODS: Twenty nine children on vigabatrin (mainly as add on therapy) were followed up for 6.5 years. Ophthalmic examination was performed before starting treatment and then six monthly in the outpatient clinic. RESULTS: Twenty one children fulfilled the inclusion criteria. Most had epileptic syndromes with infantile spasms—namely West syndrome, Lennox–Gastaut syndrome, and partial seizures. Vigabatrin dose was 25–114 mg/kg/day (mean 55.8); duration of therapy was 6–85 months (mean 35.7). Four children (19%) developed eye changes (retinal pigmentation, hypopigmented retinal spots, vascular sheathing, and optic atrophy). Visual evoked potentials were abnormal in 16 children. Electroretinography and electro-oculography, which could have picked up eye changes in early stages, were not performed, as this facility was not available. CONCLUSIONS: Vigabatrin causes eye damage. Most children with epileptic syndromes on vigabatrin cannot complain of their eye problems, hence 3–6 monthly ophthalmic follow up is strongly advised, along with regular electroretinography, electro-oculography, and visual evoked potentials if possible.